2016
DOI: 10.1111/head.12984
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Topographical Pressure Pain Sensitivity Maps of the Scalp Between Patients With Migraine and Healthy Controls

Abstract: We found that patients with migraine exhibited generalized pressure pain hypersensitivity in the head as compared to healthy controls and that hypersensitivity was similar between episodic/chronic and unilateral/bilateral migraine. Topographical pressure pain sensitivity maps revealed an anterior to posterior gradient of pressure pain sensitivity in both migraine and control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…By performing a carefully conducted blinded cross-over experiment as described in Supplementary Figure S1 , we did not reveal any unilaterality, or effect of repeated stimulus application. Accordingly, we would describe the pressure sensitivity as bilateral in location, a feature of migraine headache that is not uncommon in migraine patients 27 . Typically, researchers including Oshinsky and coworkers 13 , use von Frey monofilaments to assess cutaneous mechanical hypersensitivity within the trigeminal nerve branches, including the periorbital area.…”
Section: Discussionmentioning
confidence: 99%
“…By performing a carefully conducted blinded cross-over experiment as described in Supplementary Figure S1 , we did not reveal any unilaterality, or effect of repeated stimulus application. Accordingly, we would describe the pressure sensitivity as bilateral in location, a feature of migraine headache that is not uncommon in migraine patients 27 . Typically, researchers including Oshinsky and coworkers 13 , use von Frey monofilaments to assess cutaneous mechanical hypersensitivity within the trigeminal nerve branches, including the periorbital area.…”
Section: Discussionmentioning
confidence: 99%
“…Topographical pressure pain sensitivity maps have also been applied to investigate spatial changes in sensitivity to pressure; not just within the same muscle, but also in a particular anatomical area including the scalp, 37 , 38 shoulder, 19 , 23 elbow, 26 hand, 25 low back, 21 knee, 29 foot, 28 and the entire lower extremity. 30 These studies included different pain populations such as nummular headache, 37 migraine, 38 breast cancer survivors, 19 subacromial pain syndrome, 23 lateral elbow pain, 26 carpal tunnel syndrome, 25 knee osteoarthritis, 29 fibromyalgia syndrome, 28 and in asymptomatic adults 21 or soccer players. 30 …”
Section: Studies Reporting Topographical Pressure Pain Mapsmentioning
confidence: 99%
“…For instance, it has been found that the anterior part of the scalp is more sensitive to pressure than the middle and posterior parts in both headache patients and asymptomatic controls. 37 , 38 In the elbow area, topographical pressure pain sensitivity maps have shown that the extensor carpi radialis brevis is the most sensitive muscle of the wrist extensors in both adults with unilateral epicondylalgia and asymptomatic controls. 26 Similarly, topographical pressure pain sensitivity maps supported that the medial side of the knee joint 29 or the vastus medialis muscle 30 are the most sensitive areas of the lower extremity in both patients with painful knee osteoarthritis and professional soccer players.…”
Section: Studies Reporting Topographical Pressure Pain Mapsmentioning
confidence: 99%
“…However, the pathophysiology of CH is complex, and the underlying mechanisms are not completely understood. It is known that other primary headaches, such as migraine and tension‐type headache, are associated with hyperalgesic and allodynic responses to different stimuli. In CH, previous studies have also reported the presence of cutaneous allodynia and decreased pressure and thermal pain thresholds within the cephalic region.…”
Section: Introductionmentioning
confidence: 99%